Retraction: The effect of human capital on performance of East African commercial banks - Muhammad Zia Aftab Khan (Banks and Bank Systems, 2020)
Retracted on the 7th of July, 2020 by the Journal’s Editor-in-Chief request dated July 3th 2020. The type of retraction – plagiarism. The Editor-in-Chief of the journal was asked to retract this article because of plagiarism. The request came from the author of the article, which was published 8 months before the retracted article was published in “Banks and Bank Systems” journal. The author(s) insisted that the article completely repeated his own, i.e. contained a high level of plagiarism that could not be corrected. Editorial staff carried out an investigation into plagiarism in the article published. When the manuscript was submitted to the Journals for consideration, the authors signed the Cover letter and attested to the fact that their manuscript is an original research and has not been published before. After that, the manuscript was accepted for consideration by the Managing Editor and was tested for plagiarism using the iThenticate program. Plagiarism was not detected. Later, after the article complaint and the statement of plagiarism, we used all the sources and resources provided by the complainant, the article was re-tested for plagiarism, and plagiarism was established According to the results of the investigation, the editorial board decided to retract the article on July 7, 2020. The authors were notified of such a decision.